Nanoscale phase mixture in uniaxial strained BiFeO3 (110) thin films - Liu, Huajun (2015)
A strain-induced nanoscale phase mixture in epitaxial BiFeO3 (110) films is investigated. High resolution synchrotron x-ray diffraction shows that a monoclinic M2 phase (orthorhombic-like, with a c/a ∼ 1.01) coexists as the intermediate phase between monoclinic M1 phase (tetragonal-like, with a c/a ∼ 1.26) and monoclinic M3 phase (rhombohedral-like, with a c/a ∼ 1.00), as the film thickness increases from 10 to 190 nm. Cross-sectional transmission electron microscopy images reveal the evolution of domain patterns with coexistence of multiple phases. The different ferroelectric polarization directions of these phases, as shown by piezoelectric force microscopy, indicate a strong potential for high electromechanical response. The shear strain ϵ13 is found to be a significant driving factor to reduce strain energy as film thickness increases, according to our theoretical calculations based on the measured lattice parameters. The nanoscale mixed phases, large structure distortions, and polarization rotations among the multiple phases indicate that (110)-oriented epitaxial films provide a promising way to control multifunctionalities of BiFeO3 and an alternative direction to explore the rich physics of perovskite system.